Psychotic-Like Experiences and Their Cognitive Appraisal Under Short-Term Sensory Deprivation - Daniel, Christina; Lovatt, Anna; Mason, Oliver John (Frontiers in Psychiatry, 2014)
Aims: This study aimed to establish and compare the effects of brief sensory deprivation on individuals differing in trait hallucination proneness. Method: 18 participants selected for high hallucination-proneness were compared against 18 participants rating low on this trait. The presence of psychotic-like experiences, and participants’ cognitive appraisals of these, was evaluated in three different settings: at baseline, in a ‘secluded office’ environment, and in light-and-sound sensory deprivation. Results: Psychotic-like experiences were experienced significantly more often in sensory deprivation for both groups. In particular both experienced slight increases in perceptual distortions and anhedonia in seclusion, and these increased further during sensory deprivation. Highly hallucination prone individuals showed a significantly greater increase in perceptual distortions in sensory deprivation than did non-prone individuals suggesting a state-trait interaction. Their appraisals of these anomalous experiences were compared to both clinical and non-clinical individuals experiencing psychotic symptoms in everyday life. Conclusion: Short-term sensory deprivation is a potentially useful paradigm to model psychotic experiences, as it is a non-pharmacological tool for temporarily inducing psychotic-like states and is entirely safe at short duration. Experiences occur more frequently, though not exclusively, in those at putative risk of a psychotic disorder. The appraisals of anomalous experiences arising are largely consistent with previous observations of non-clinical individuals though importantly lacked the general positivity of the latter.